Compreensões acerca da utilização da história da ciência na educação básica - Waldow, Andressa Morais (2019)
This article presents a concluding work of the Chemistry Degree Course of the Federal University of Fronteira Sul (UFFS) - Cerro Largo/RS campus, which is a research focused on the use of the history of science (HC) in teaching, having as objects of study academic research and understandings of teachers of Basic Education (EB) on the subject. Therefore, it aims to analyze understandings present in the academic literature and in teacher speeches, seeking to identify how the insertion of HC in Basic Education occurs. The study is of a qualitative nature carried out in two stages, one being documentary and the other empirical. Through the analysis process, few studies were identified that investigate aspects of HC in teacher training. It was also observed that aspects of HC have been worked on in classes in the area of Nature Sciences, but with some challenges to be overcome, among which stands out the lack of historical information. Also, three categories were identified that emerged from the analysis of the teachers' responses, namely: critical, traditional and practical. The critical category indicates understandings of the importance of the use of HC for the development of critical thinking of the student. In the traditional category, on the other hand, comprehensions were allocated that show misunderstandings regarding the vision of Science, being considered an absolute truth. And the third category, practice, was identified in the understandings that are in the process of evolution, i.e., teachers understand the importance of HC as an instrument that helps students to understand the world around them. With the study, the importance of expanding studies on HC in teacher education is pointed out. Finally, the realization of this work enabled the understanding of the importance of the insertion of historical contents in the teaching of science in the classroom in order to deconstruct an absolutist view of science, which can contribute to the development of critical thinking in the classroom.